2022
DOI: 10.1007/s10787-022-01070-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of lipoxin in the management of COVID-19: a narrative review

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection leads to the development of coronavirus disease 2019 (COVID-19), which causes endothelial dysfunction (ED), oxidative stress (OS), and inflammatory disorders. These changes cause hypoxia and cytokine storm with the development of cardio-pulmonary complications. Bioactive lipids and other polyunsaturated fatty acids participate in a vital role in the SARS-CoV-2 infection process. One of these mediators is the anti-inflammatory compound, lipoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 81 publications
0
25
0
Order By: Relevance
“…In vitro study observed that SRT-1720 was not toxic to cell lines. Recently, SRT-1720 was effective in AD through the modulation of mitochondrial autophagy and biogenesis via the SIRT1-dependent pathway (Shukla et al 2016 ; Batiha et al 2022 ). Therefore, SRT-1720, through activation of SIRT1, could be a promising future therapy in the management of PD.…”
Section: Role Of Sirt1 Activators In Pdmentioning
confidence: 99%
“…In vitro study observed that SRT-1720 was not toxic to cell lines. Recently, SRT-1720 was effective in AD through the modulation of mitochondrial autophagy and biogenesis via the SIRT1-dependent pathway (Shukla et al 2016 ; Batiha et al 2022 ). Therefore, SRT-1720, through activation of SIRT1, could be a promising future therapy in the management of PD.…”
Section: Role Of Sirt1 Activators In Pdmentioning
confidence: 99%
“…The fusion protein of the SARS‐CoV‐2 spike protein is enhanced by Ca 2+. 59,60 These findings suggest that Ca 2+ is necessary for binding, entry and invasion of SARS‐CoV‐2. SARS‐CoV‐2 entry is associated with activation of endosomal Ca 2+ channels, which are necessary for uptake of SARS‐CoV‐2.…”
Section: Role Of Ryanodine Receptors and Dantrolene In Covid‐19mentioning
confidence: 91%
“…Maresin1 and its epoxide intermediate 13S, 14S-epoxi-DHA, enhance the macrophage conversion from M1 to M2 phenotype, it is well known that M2 are pro-resolving in nature, enhance macrophage phagocytosis and efferocytosis ( Freedman et al, 2020 ). Lipoxins (LXs) might reduce the inflammatory changes that occur due to activation of MAPK, mTOR, and NLPR3 inflammasome in COVID-19, reduce tumor necrosis factor-alpha and interferon-gamma secretion, block T cell migration and promote T cell apoptosis ( Batiha et al, 2022 ). Neuroprotectin D1/Protectin reduce PMN infiltration through endothelial cells and stimulate the removal of apoptotic cells by MΦ t have crucial hereby play a crucial role in managing diseases such as Alzheimer’s disease ( Rajasagi et al, 2013 ; Mohammed et al, 2022 ).…”
Section: Spms In Regulation Of Inflammatory Macrophages In Covid-19mentioning
confidence: 99%
“…Lipoxins (LXs), can inhibition of viral entry and its replication, downregulate ACE2 receptors, inhibit release of the pro-inflammatory cytokines. Moreover, LXs can augment the polarization of macrophages from (M1) to (M2) phenotype, causing a shift from pro-inflammatory to anti-inflammatory environment, thereby enhancing the inflammation resolving actions of macrophages in SARS-CoV-2 infection ( Das, 2021 ; Batiha et al, 2022 ). RvE1and RvE4 enhances macrophage phagocytosis and efferocytosis of senescent erythrocytes that characterize COVID-19 ( Libreros et al, 2021 ).…”
Section: Spms In Regulation Of Inflammatory Macrophages In Covid-19mentioning
confidence: 99%